Influence of FKBP5 Variants and Childhood Trauma on Brain Volume in Non-clinical Individuals - Kwon, Aeran; Kim, Sungkean; Jeon, Hyeonjin; Lee, Hyun Seo; Lee, Seung-Hwan (Frontiers in Behavioral Neuroscience, 2021)
The present study aimed to investigate the possible influence of childhood trauma and its interaction effect with 10 SNPs of FKBP5 gene on brain volume in non-clinical individuals. One hundred forty-four non-clinical volunteers (44 men and 100 women) were genotyped with respect to 10 variants (rs9296158, rs3800373, rs1360780, rs9470080, rs4713916, rs4713919, rs6902321, rs56311918, rs3798345 and rs9380528) of FKBP5. Participants underwent MRI scan and psychological assessments such as the childhood trauma questionnaire, hospital anxiety and depression scale, rumination response scale and quality of life assessment instrument. Individuals with the high CTQ score showed enlarged volume of the left orbitofrontal cortex (OFC) if they have childhood trauma-susceptible genotype of FKBP5 rs3800373, rs1360780, rs4713916, rs4713919, rs6902321 and rs3798345 and enlarged volume of the left middle temporal gyrus (MTG) if they have childhood trauma-susceptible genotype of FKBP5 rs3800373, rs1360780, rs4713916, and rs3798345. Among those with the childhood trauma-susceptible genotype, the left OFC and left MTG showed significant negative correlations with positive feelings about life, and the left OFC showed significant positive correlations with negative cognition. This is one of the few studies to identify the volume alteration of the left OFC and the left MTG for the FKBP5 gene-childhood trauma interaction in non-clinical individuals.